2017
DOI: 10.1149/2.0801714jes
|View full text |Cite
|
Sign up to set email alerts
|

Graphite/MnO2and MoS2Composites Used as Catalysts in the Oxygen Reduction Cathode of Microbial Fuel Cells

Abstract: In this study, mixtures of graphite, γ-MnO 2 and MoS 2 with different weight proportions (20:1:1, 30:1:2 and 30:2:1) were used in microbial fuel cells (MFCs) and the catalysts were also subjected to ultrasonication to study its influence. The data suggest that the MFC fabricated with the catalyst prepared using graphite, γ-MnO 2 and MoS 2 in a weight proportion of 20:1:1 exhibited the highest optimal power density of 120 mW/m 2 . However, after ultrasonic treatment, the power density was significantly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Jiang et al investigated the performance of MnO 2 and its combination with MoS 2 (real wastewater). The best combination of MnO 2 and MoS 2 revealed peak power densities of up to 165 mW/m 2 [9,14]. Another investigated composition within this study was MoS 2 , which is sparsely described in literature.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Jiang et al investigated the performance of MnO 2 and its combination with MoS 2 (real wastewater). The best combination of MnO 2 and MoS 2 revealed peak power densities of up to 165 mW/m 2 [9,14]. Another investigated composition within this study was MoS 2 , which is sparsely described in literature.…”
Section: Introductionmentioning
confidence: 75%
“…A following study with flower-like Co 3 O 4 and lower COD loads (digester sludge and acetate) showed lower maximum power densities of 248 mW/m 2 [15]. Our working group already demonstrated the long-term stability of MnO 2 [14] , MoS 2 [9], and Co 3 O 4 [37] electrodes. It was shown that MnO 2 , MoS 2 , and Co 3 O 4 have decent ORR properties and fulfill the requirements of MFC cathodes-they are inexpensive, long-term stable, environmentally friendly [38,39], reduce the overvoltage, and are immune to catalyst poising.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations